Geochemistry of Silurian-Devonian alkaline basalt suites from the Gaspé Peninsula, Quebec Appalachians - Laurent, R.; Bélanger, J. (Atlantic Geology)

(untitled) (Maritime Sediments Editorial Board, 1984)
Products of Late Silurian and Early Devonian volcanism in the Northern Appalachians are well exposed in the Chaleurs Bay area of the Gaspe Peninsula. The volcanic association Is dominated by plagioclase basalts and andesltes, and includes pyroclastic flows of dacltic and rhyolitic composition. Major and trace-element chemical analyzes of 174 rocks show that the volcanic association derives from alkaline and high-alumina basalt magmas. The basalts are usually olivine normative and high in A1303, TiOa, P2Os and in incompatible elements such as Y and Zr. They follow the course of a calc-alkaline differentiation trend. This volcanism is interpreted to have been related genetically to a regime of tectonic compression, and controlled structurally by fault zones. The Quaternary volcanism associated with the major transcurrent fault zones of northern Anatolia and Iran within the Alpine Orogen provides a modern analog to the Silurian-Devonian volcanism of the Gaspe Peninsula and Newfoundland.